Computer vision in surgery: from potential to clinical value - Mascagni, Pietro; Alapatt, Deepak; Sestini, Luca; Altieri, Maria S.; Madani, Amin; Watanabe, Yusuke; Alseidi, Adnan; Redan, Jay A.; Alfieri, Sergio; Costamagna, Guido; Boškoski, Ivo; Padoy, Nicolas; et al. (NPJ digital medicine, 2022)
Hundreds of millions of operations are performed worldwide each year, and the rising uptake in minimally invasive surgery has enabled fiber optic cameras and robots to become both important tools to conduct surgery and sensors from which to capture information about surgery. Computer vision (CV), the application of algorithms to analyze and interpret visual data, has become a critical technology through which to study the intraoperative phase of care with the goals of augmenting surgeons’ decision-making processes, supporting safer surgery, and expanding access to surgical care. While much work has been performed on potential use cases, there are currently no CV tools widely used for diagnostic or therapeutic applications in surgery. Using laparoscopic cholecystectomy as an example, we reviewed current CV techniques that have been applied to minimally invasive surgery and their clinical applications. Finally, we discuss the challenges and obstacles that remain to be overcome for broader implementation and adoption of CV in surgery.